Faktor - Faktor Yang Mempengaruhi Ekspor CPO Sumatera Utara - Faoeza Hafis Saragih; Dwidjono Hadi Darwanto; Mashyuri Mashyuri (Universitas Medan Area, 2018)
This study was aimed to determine factors that affect CPO export in North Sumatra. This research was mainly based on to increase export volume and economic growth of Indonesia and specially North Sumatera beside to develop CPO industry. Secondary data of the time period of the years 1980-2010 were applied in the analyses and collected from BPS, Ministry of Agriculture and KPB PTPN. Ordinary least square (OLS) model used to see the factors that affected CPO export of North Sumatra. The results of study show that North Sumatera CPO exports was affected positively by Dollar exchange rate against Rupiah. It was causes the exporters gets a lot advantages from differences from Dollar exchange against Rupiah. The government have two assignment against, first make a policy to develop CPO export and the second make policy to protect the industries in Indonesia that used CPO as a raw materials. Keywords: Affected, CPO, Export